Emotions and Multilingualism in L1 isiXhosa speakers: Measuring emotional resonance reduction using the RER-LX scale - Hall, Jessica (Stellenbosch : Stellenbosch University, 2026)
Thesis (MA)--Stellenbosch University, 2026.